REVIEW - Williams, Howard; Giles, Melanie (Kronos: Southern African Histories, 2020)
Archaeology is a practice concerning time. Layer upon layer of earth condenses to become the ground on which generation after generation lives and dies. Human remains are among the many objects that fill the soil, and some of them get ‘discovered’, exhumed, researched and displayed by archaeologists across the world. For the edited volume, Archaeologists and the Dead, editors Howard Williams and Melanie Giles convened a collection of authors who take seriously the scientific, metaphoric, historical and political implications of the work of digging. With the exception of a study from the island of Saint Helena, the authors write exclusively about sites in the United Kingdom, northern and western Europe and North America, using these as a base from which to evaluate contemporary archaeological and museum practices regarding human remains. Their perspectives could certainly have been enriched and challenged by authors and case studies from the global South. Reading the book from a South African context, one cannot but think of local examples where the politics surrounding human remains speak directly to colonial, slave and apartheid histories.1 Voices from the global South would have added instructive methodologies and theories for thinking through the current moment in the discipline of archaeology. The book has three parts. The first, ‘Investigating the Dead’, explores archaeological processes. Written mostly by practicing archaeologists, it centres on their methodological concerns. The second, ‘Displaying the Dead’, examines the politics of the dead body in the context of museums. The third, ‘Public Mortuary Archaeology’, presents ‘wider accounts of interactions between society, media, and mortuary archaeology’ (13). This third part considers the social meanings produced by archaeological excavations of human remains in contemporary society. My own interests lie in three themes that arc across the book’s three sections, and it is through these that I offer some observations on this wide-ranging collection. My review traverses the tensions between ‘science’ and ‘fiction’, ‘the individual’ and ‘the collective’, as well as the ‘recent’ and ‘ancient’ dead. Just as, over time, bodies become indivisible from the soil in which they are buried, so too do these categories become ever more porous and entangled.